2020
DOI: 10.1097/inf.0000000000002808
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Manifestations of Congenital Cytomegalovirus Infection in a Screening Program in Madrid (PICCSA Study)

Abstract: Background: Cytomegalovirus (CMV) is the leading cause of congenital infection worldwide. Up to 15%–20% of infected newborns will develop long-term sequelae such as hearing loss and neurologic abnormalities. The aim of this study was to investigate the prevalence of congenital CMV infection (cCMV) and associated clinical abnormalities in Spain. Methods: A prospective screening for cCMV by viral load in saliva was performed. Saliva samples were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 26 publications
3
36
0
7
Order By: Relevance
“…The prevalence of cCMV in our study is very similar to that reported in Portugal, and far from the 0.6% that has been described in a meta-analysis in high-income countries [3]. Unfortunately, historical estimates of cCMV to compare with from our region are not available, but a recent study in Madrid reported a 0.47% prevalence rate [4]. It is likely that the lockdown measures and behavioral interventions to reduce SARS-CoV-2 transmission in Spain during 2020-2021 also impacted on CMV transmission and cCMV prevalence.…”
supporting
confidence: 85%
“…The prevalence of cCMV in our study is very similar to that reported in Portugal, and far from the 0.6% that has been described in a meta-analysis in high-income countries [3]. Unfortunately, historical estimates of cCMV to compare with from our region are not available, but a recent study in Madrid reported a 0.47% prevalence rate [4]. It is likely that the lockdown measures and behavioral interventions to reduce SARS-CoV-2 transmission in Spain during 2020-2021 also impacted on CMV transmission and cCMV prevalence.…”
supporting
confidence: 85%
“…The kappa value between saliva and urine testing was low (0.31) in a study from Indonesia [30] . Inconsistent saliva and urine results were also reported in studies from Spain and Germany [ 31 , 32 ]. The discrepant results were obtained from populations in different regions, where the dominant infection types (primary infection, reinfection or reactivation) in pregnant women are potentially very different.…”
Section: Discussionmentioning
confidence: 57%
“…Of these newborns, the majority had a low viral load in saliva or urine. The nonnegligible false-positive result in screening is an issue also reported in other studies [ 19–22 ], which is the reason to recommend confirmatory testing using subsequent samples in the current consensus [ 1 , 23 ]. Herein, we confirmed the newborns’ cCMV status according to the consensus’s suggestion; however the long-term clinical outcomes of these questionable newborns will be followed up in the future to better understand their cCMV status.…”
Section: Discussionmentioning
confidence: 87%